2022
DOI: 10.1016/j.diabres.2021.109170
|View full text |Cite
|
Sign up to set email alerts
|

Irisin rescues diabetic cardiac microvascular injury via ERK1/2/Nrf2/HO-1 mediated inhibition of oxidative stress

Abstract: Cardiac microvascular dysfunction is a common feature across cardiovascular complications in diabetes, while effective therapy remains elusive. This study was designed to evaluate the effect of irisin on cardiac microvascular injury in type 2 diabetes mellitus (T2DM).Methods: T2DM was induced in C57BL/6J mice. A cohort diabetic mice received a 12-week treatment of irisin. Cardiac function and microvessel density were evaluated. Whether irisin directly regulates cardiac microvascular endothelial cells (CMECs) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…To further verify the role of ferroptosis on irisin-mediated protection of DCM in T1DM in mice, we administered the ferroptosis inducer erastin (40 mg/kg body weight/day, for 3 consecutive days) to STZ-induced diabetic mice [ 35 ]. The protective effects of irisin on the heart of STZ-induced diabetic mice included improvement in cardiac function, mitigation of pathological structure disorder and fibrosis, and restoration of mitochondrial structure in cardiomyocytes.…”
Section: Resultsmentioning
confidence: 99%
“…To further verify the role of ferroptosis on irisin-mediated protection of DCM in T1DM in mice, we administered the ferroptosis inducer erastin (40 mg/kg body weight/day, for 3 consecutive days) to STZ-induced diabetic mice [ 35 ]. The protective effects of irisin on the heart of STZ-induced diabetic mice included improvement in cardiac function, mitigation of pathological structure disorder and fibrosis, and restoration of mitochondrial structure in cardiomyocytes.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Khorasani et al showed that irisin levels were relatively lower in diabetic patients with cardiovascular complications in comparison to uncomplicated diabetic patients [ 43 ]. On the contrary, other studies concluded that increased irisin levels mediate cardioprotection in diabetic subjects and inhibit myocardial apoptosis, implicating irisin as a potential therapeutic intervention during diabetic cardiomyopathy [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, oxidative stress facilitates the occurrence and development of vascular calcification through NADPH oxidase and its downstream ERK signaling pathway (93). By activating Nrf2/HO-1 signaling pathway, irisin could increase the expression of key antioxidant enzymes, such as catalase-9, superoxide dismutase, and glutathione peroxidase, and inhibit the production of hydrogen peroxide, so as to protect vascular endothelial cells from cellular oxidative damage (94). Irisin has been clearly confirmed to have an antioxidant function, and the antioxidant mechanism of irisin is associated with important cellular processes by reducing ROS and its complications, including regulation of mitochondrial fission and fusion, inhibition of inflammasome activation, improvement of autophagy, inhibition of endoplasmic reticulum stress and ferroptosis, and reversal of cell death (95).…”
Section: Irisin and Oxidative Stressmentioning
confidence: 99%